Modern possibilities of using immunotherapy in the treatment of cervical cancer - A. V. Tarasova; K. A. Ganina; M. A. Meshkova; Yu. V. Solovyeva; E. E. Ivanova; L. N. Akimov (Опухоли женской репродуктивной системы)
Cervical cancer (CC) is the fourth most common cancer in women worldwide. Every year, more than 500,000 women are diagnosed with CC, and the disease leads to more than 300,000 deaths worldwide. Infection with the human papillomavirus is the cause of CC in most cases. The disease is largely preventable through preventive vaccination. Approximately 90 % of CC cases are diagnosed in low-and middle-income countries where there are no organized human papillomavirus screening and vaccination programs. A special group in this disease consists of patients who develop recurrent / metastatic CC. To date, the most promising direction of drug treatment for this pathology is drugs that act on the control points of immunity – the PD-1 receptor / PD-L1 ligand, which are used by the tumor to block the immune system. The article presents a clinical case demonstrating the efficacy of the PD-1 inhibitor pembrolizumab for the treatment of recurrent / metastatic CC.